DIGITAL SIGNAGE SEBAGAI INFORMASI INTERAKTIF MASJID NURUL IMAN BERBASIS WEB RESPONSIVE - Dawis, Aisyah Mutia; Murhadi, Murhadi (Universitas Aisyiyah Surakarta, 2023)
Information technology is anything that helps humans in creating, changing, storing, communicating or disseminating information. In human life, there are social relationships that cannot be separated from technology, especially information technology media. Presenting information is no longer using print media intermediaries, but has shifted to the use of electronic digital media. Submission of information can be interpreted as an announcement or message conveyed to everyone who is the goal or target of the information in question. This study discusses Digital Signage (announcement information system) which replaces conventional announcement media / wall magazine boards into digital form. This form of Digital Signage is used in computers by connecting to a monitor to display digitally based information in one direction. This announcement information makes the administrators of the Nurul Iman Mosque no longer need to print and paste announcements on the available information boards, but can enter the announcement digitally into the system and then the announcement will automatically appear on the monitor screen available in the Nurul Iman Mosque area. This can make the process of delivering information more effective and efficient when compared to print media as well as more interesting and interactive.